Treatment of periodontal disease: does drug delivery matter? - Lima de Sousa, Tarcílio; Dourado, Douglas; Rodrigues, Júlia Soares; de Souza Rebouças, Juliana; Montes, Marcos Antônio Japiassú Resende; Formiga, Fabio Rocha (Frontiers in Bioengineering and Biotechnology, 2024)
Graphical Abstract